BaB2O3F2: A Barium Fluorooxoborate with a Unique 2∞ [B2O3F]− Layer and Short Cutoff Edge. Issue 27 (25th April 2019) - Huang, Chunmei; Zhang, Fangfang; Li, Hao; Yang, Zhihua; Yu, Haohai; Pan, Shilie
Abstract: Substitution of oxygen by fluorine in the borate group offers a materials platform from which intriguing structure and functionality may arise. Herein, we report a new fluorooxoborate, BaB2 O3 F2, synthesized by introducing the F atoms into the BaO–B2 O3 system. BaB2 O3 F2 exhibits a unique oxyfluoride layer 2 ∞ [B2 O3 F] − and a deep‐ultraviolet cutoff edge below 180 nm. The effect of the introduction of F atoms on the structure and optical property of the borate group has been investigated; this should be useful to further expand borate chemistry and materials. Abstract : Crystal growth : 2 ∞ [B2 O3 F] − and 2 ∞ [BaF] + layers alternately arranged parallel to the ab plane to generate the 3D structure of BaB2 O3 F2 (see figure)